2009
DOI: 10.1016/j.jneb.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Behavior and Infant Weight Gain in the First Year

Abstract: The risk for overweight for low-income Hispanic children younger than age 5 in the United States is significantly higher than for non-Hispanic blacks, which in turn is higher than for nonHispanic whites (1,2). Using the criterion of a Body Mass Index (BMI) ≥ the 95 th percentile for age and sex for defining overweight, the prevalence among low-income young children age 2-4 years in the US as of the year 2000 was around 19% (3). Though the sample was not nationally representative, a review of over 20 years of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 34 publications
4
96
0
3
Order By: Relevance
“…In support of this contention, Worobey et al (2009) noted that mothers' lower sensitivity to infant's feeding cues at 6 months was positively associated with infants' higher weight gain at 12 months. Brown and Lee (2011) demonstrated that lower levels of responsiveness to a child's needs were positively associated with higher child weight gain at the age of 2 years.…”
Section: Introductionmentioning
confidence: 88%
“…In support of this contention, Worobey et al (2009) noted that mothers' lower sensitivity to infant's feeding cues at 6 months was positively associated with infants' higher weight gain at 12 months. Brown and Lee (2011) demonstrated that lower levels of responsiveness to a child's needs were positively associated with higher child weight gain at the age of 2 years.…”
Section: Introductionmentioning
confidence: 88%
“…Excessive maternal control during feedings may interfere with infant"s ability to self-regulate intake and display clues of satiety, [15] and have been associated with unhealthy feeding and weight gain in children. [16][17][18] A study of 368 Latina mothers participating in WIC programs reported that 50% of the participants described tendencies toward more "pressure feeding" or controlling maternal feeding patterns, as they always promoted bottle bottleemptying practices. [19] Maternal controlling feeding patterns may contribute to higher energy intake and thus represent an important preventable and modifiable risk factor for the prevention of obesity in early childhood.…”
Section: Modifiable Feeding Factors By Overweight Statusmentioning
confidence: 99%
“…Overfeeding may arise from insensitivity to fullness cues, the use of food to comfort (Worobey et al, 2009) as some infants have a more avid appetite than others (Lumeng, 2016). In turn, mothers may restrict intake for children they perceive to over-eat, or may pressure children with small appetites to eat more (Webber et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%